Method for preparing high-performance low-carbon red mud-based geopolymer
By combining the calcined Bayer red mud with slag powder and polymer composition, the problem that Bayer red mud is difficult to prepare high-performance polymers in the prior art is solved, and the effect of high strength and heavy metal ion curing is achieved. Improves the environmental performance of the material.
Patent Information
- Application Number
- CN202411806112.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art is difficult to effectively use Bayer red mud to prepare high-performance polymers, and the free volatility of heavy metal ions in the red mud causes pollution to the environment.
By pulverizing and calcining the dried Bayer mud and mixing it with slag powder as gelling material with aggregate, alkali trigger and polymer composition (from hydroxypropylethylcellulose, polyethylene oxide and ethylene-vinyl acetate). Copolymer composition) is used together to prepare high-performance low-carbon red mud base polymers.
Bayer red mud has excellent bending and flexural strength at a high proportion, and at the same time effectively cures heavy metal ions, reduces their dissolution and diffusion, and significantly improves the environmental protection performance of the prepared ground polymer.
Smart Images

Figure CN119430773A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geopolymer building material preparation, and in particular to a method for preparing a high-performance low-carbon red mud-based polymer. Background Art
[0002] Red mud is a solid waste produced by the separation of red mud slurry obtained after bauxite is dissolved under high temperature and high pressure during the production of alumina. The waste has a high iron oxide content and is red in appearance, so it is called red mud. Red mud contains a large amount of alkali liquid. Large amounts of red mud storage are prone to alkali leakage. There are a large number of fluoride ions, sodium ions and heavy metal ions in the alkali liquid, which will cause pollution of underground surface water and salinization of surrounding soil. The exposed dry red mud surface is prone to dust formation, polluting the surrounding environment.
[0003] The pH value of red mud is between 12 and 14. It has a large specific surface area and complex composition. Each component exists in the form of silicon slag and does not conform to the mineral composition of natural soil. It is an insoluble residue and its resource utilization is severely restricted. Therefore, the treatment of red mud has become an international problem.
[0004] The research on the resource utilization of red mud mainly focuses on the recovery of valuable metals, adsorption materials, soil remediation, building materials, catalysts and new functional materials. Among them, the research on building materials is most likely to achieve the method of large-scale resource utilization of red mud. Geopolymers, as a new type of inorganic non-metallic material, use solid wastes such as red mud, slag, fly ash as raw materials to prepare building materials. They have the advantages of high early strength, fast setting speed, acid resistance, corrosion resistance and good interface bonding ability. It can replace cement, which not only reduces CO2 emissions (CO2 emissions from cement production account for about 7% of the global total emissions), reduces environmental pollution, but also enables solid waste to be utilized as a resource.
[0005] Existing red mud geopolymers are divided into binary or multi-component geopolymers composed of red mud and fly ash, slag, kaolin, lime, etc. according to the gel material. Among them, red mud + slag-based geopolymers have been studied more. Compared with other geopolymers, red mud + slag-based geopolymers have higher strength and can meet the needs of building materials. Red mud is divided into Bayer red mud and sintered red mud according to different production processes. The existing technology prepares geopolymers from Bayer red mud and sintered red mud respectively. After testing, Bayer red mud is not suitable for preparing geopolymers regardless of whether it has been calcined. Since the activity of Bayer red mud is low, the strength of the formed geopolymer is low. High-temperature calcination can improve the strength of the geopolymer to a certain extent, but the effect is not ideal. Summary of the invention
[0006] Based on the existing technical problems, the present invention aims to provide a method for preparing high-performance low-carbon red mud-based polymers. High-strength geopolymers are prepared using Bayer red mud as raw materials. In addition, heavy metal ions in red mud are effectively solidified, reducing the free volatilization of heavy metal ions in geopolymers and causing environmental pollution.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high-performance low-carbon red mud-based polymer includes the preparation of a slurry, characterized in that the slurry is prepared by crushing dried Bayer red mud and then calcining it, mixing the calcined red mud with slag powder as a cementitious material, mixing the cementitious material, aggregate, alkali activator and external additives, adding water and stirring evenly to form a slurry.
[0008] Furthermore, the calcination is to calcine the crushed Bayer red mud at 600-800° C. for 1-2 h, and then naturally cool it to room temperature.
[0009] Further preferably, the calcination is to calcine the crushed Bayer red mud at 600° C. for 2 h, and then naturally cool it to room temperature.
[0010] Furthermore, in the cementitious material, the mass ratio of Bayer red mud to slag powder is 0.4: 0.6~0.7:0.3, and the slag powder is at least one of S95 slag powder and S105 slag powder.
[0011] The specific surface area of the slag powder is ≥400m 2 / kg, flow ratio ≥95%, in line with standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".
[0012] Furthermore, the aggregate is standard sand, specifically IS0 standard sand.
[0013] Furthermore, the alkaline activator is instant sodium silicate powder, and sodium hydroxide is added to adjust the solution modulus to 1.0-2.5.
[0014] Furthermore, the external additives include a water reducing agent, a retarder, an expansion agent and a polymer composition.
[0015] Furthermore, the water reducer is at least one of sodium lignin sulfonate, polycarboxylic acid water reducer, naphthalene-based water reducer and melamine-based water reducer.
[0016] Furthermore, the retarder is at least one of sodium gluconate, boric acid, sucrose, calcium stearate, dodecyltrimethoxysilane, desulfurized gypsum, etc.
[0017] Furthermore, the expansion agent is at least one of UEA type and AEA type concrete expansion agent.
[0018] Furthermore, the polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer.
[0019] Furthermore, the addition amount of each component in the polymer composition is based on the mass of the gelling material, and calculated by mass percentage, the doping amount is 0.05%-0.5% of hydroxypropyl ethyl cellulose, 0.05%-0.4% of polyethylene oxide and 0.5%-3% of ethylene-vinyl acetate copolymer.
[0020] Furthermore, in the polymer composition, the molecular weight of hydroxypropyl ethyl cellulose is 200,000 to 400,000, the molecular weight of polyethylene oxide is 6 to 8 million, and the molecular weight of ethylene-vinyl acetate copolymer is 100,000 to 200,000.
[0021] Further preferably, the doping amount of each component in the polymer composition is 0.2% hydroxypropyl ethyl cellulose, 0.1% polyethylene oxide and 2.0% ethylene-vinyl acetate copolymer.
[0022] The amount of SiO2 and Al2O3 in slag is higher than that in red mud, which can meet the demand of stable geopolymer for silicon-aluminum ratio.
[0023] Since the strength and elastic modulus of red mud geopolymers decrease with the increase of red mud doping, the amount of red mud in most red mud geopolymers is less than 50%. When the doping amount is too high, the strength of the geopolymer will be significantly reduced, resulting in failure to meet the use requirements, especially Bayer red mud.
[0024] In the present invention, the strength of the geopolymer is effectively improved by adding the polymer composition, so that the geopolymer can maintain a high strength even when the red mud content increases. In addition, it is found that the addition of the polymer composition composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer in the present invention effectively enhances the heavy metal ion curing effect of the prepared geopolymer and reduces the dissolution and diffusion of heavy metal ions during the long-term use of the geopolymer.
[0025] Furthermore, in the prepared slurry, the mass ratio of cementitious material to aggregate is 1:1-3. Based on the mass of cementitious material and calculated by mass percentage, the alkali activator in the slurry is 6.5%-7.5% in terms of Na2O, the water reducer is 0.4%-1.2%, the retarder is 2%-3%, the expansion agent is 0.5%-1%, and the water-cement ratio of the slurry is 0.35-0.55.
[0026] Most specifically, a method for preparing a high-performance low-carbon red mud-based polymer is characterized by comprising the following steps: (1) Grind the dried Bayer red mud, pass it through a 40-mesh sieve, calcine it at 600-800°C for 1-2h and then cool it naturally; (2) The Bayer red mud treated in step (1) and the slag powder are mixed in a mass ratio of 0.4: 0.6-0.7:0.3 as a cementitious material, the cementitious material, the alkali activator, the water reducer, the retarder, the expansion agent and the polymer composition are mixed, water is added and stirred evenly, and then the aggregate is added and stirred evenly to form a slurry, and the water-cement ratio is 0.35-0.55; the mass ratio of the cementitious material to the aggregate is 1:1-3, and based on the mass percentage of the cementitious material, the alkali activator in the slurry is 6.5%-7.5% in terms of Na2O, the water reducer is 0.4%-1.2%, the retarder is 2%-3%, the expansion agent is 0.5%-1%, and the polymer composition is hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer. The polymer composition is composed of 0.05% to 0.5% hydroxypropyl ethyl cellulose, 0.05% to 0.4% polyethylene oxide and 0.5% to 3% ethylene-vinyl acetate copolymer; the aggregate is ISO standard sand, the alkali activator is instant sodium silicate powder, the solution modulus is adjusted to 1.0 to 2.5 with sodium hydroxide, the water reducer is at least one of sodium lignin sulfonate, polycarboxylic acid water reducer, naphthalene water reducer, melamine water reducer, the retarder is at least one of sodium gluconate, boric acid, sucrose, calcium stearate, dodecyl trimethoxy silane, desulfurized gypsum, etc., and the expansion agent is at least one of UEA type and AEA type concrete expansion agent; (3) The slurry prepared in step (2) is introduced into a mold and placed in a standard constant temperature and humidity curing box in an environment with a temperature of 21°C and a humidity of 95% for 2 hours. After demolding, it is continued to be placed in the constant temperature and humidity curing box for curing.
[0027] The present invention has the following technical effects: In the present invention, by adding a polymer composition composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer, the strength of the geopolymer is effectively improved, so that the Bayer red mud can also have excellent bending strength and flexural strength at a high ratio. At the same time, the curing effect of the geopolymer on heavy metal ions is effectively improved, and the dissolution and diffusion of heavy metal ions during long-term use are reduced. The solubility of heavy metal ions such as Cr, Cu and Ni is reduced by more than 50%, thereby improving the environmental protection performance of the prepared geopolymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : Scanning electron microscope image of the geopolymer prepared in Example 1 after being naturally placed for 60 days.
[0029] Figure 2 : Scanning electron micrograph of the geopolymer prepared by adding 0.3% hydroxypropyl ethylcellulose alone after being naturally placed for 60 days.
[0030] Figure 3 : Scanning electron micrograph of the geopolymer prepared by adding 1.0% ethylene-vinyl acetate copolymer alone after being naturally placed for 60 days.
[0031] Figure 4 : Scanning electron microscope image of the geopolymer prepared in Example 2 after being naturally placed for 60 days.
[0032] Figure 5 : Effect of hydroxypropyl ethyl cellulose (Z1) on the compressive strength of geopolymer.
[0033] Figure 6 : Curve diagram of the effect of polyethylene oxide (Z2) on the compressive strength of geopolymer.
[0034] Figure 7 : Curve diagram of the effect of ethylene-vinyl acetate copolymer (Z3) on the compressive strength of geopolymer. DETAILED DESCRIPTION
[0035] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0036] The red mud used in the present invention is Bayer red mud provided by Chongqing Jiulong Wanbo New Material Technology Co., Ltd., and includes Australian red mud and red mud from several minerals according to different mineral sources. The chemical properties of red mud from different mineral sources are shown in Table 1.
[0037] Table 1: Chemical properties of red mud from different mineral sources
[0038] In the polymer composition used in the present invention, the molecular weight of hydroxypropylethylcellulose is 200,000, the molecular weight of polyethylene oxide is 8,000,000, and the molecular weight of ethylene-vinyl acetate copolymer is 100,000.
[0039] Example 1 A method for preparing a high-performance low-carbon red mud-based polymer comprises the following steps: (1) The dried Australian Bayer red mud was crushed, passed through a 40-mesh sieve, calcined at 600°C for 2 h, and then cooled naturally; (2) The Bayer red mud treated in step (1) and the slag powder are mixed in a mass ratio of 0.5: 0.5 is mixed as a cementitious material, the cementitious material, alkali activator, water reducer, retarder, expansion agent and polymer composition are mixed, water is added and stirred evenly, and then aggregate is added and stirred evenly to form a slurry, and the water-cement ratio is 0.4; the mass ratio of cementitious material to aggregate is 1:1, based on the mass of the cementitious material, according to the mass percentage, the alkali activator is 7% calculated as Na2O, the water reducer is 0.5%, the retarder is 3%, the expansion agent is 1%, and the polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer, and the doping amounts are 0.2% hydroxypropyl ethyl cellulose, 0.1% polyethylene oxide and 2% ethylene-vinyl acetate copolymer respectively; the aggregate is ISO standard sand, the alkali activator is instant sodium silicate powder, the solution modulus is adjusted to 1.2 with sodium hydroxide, the water reducer is a naphthalene-based water reducer, the retarder is desulfurized gypsum, the expansion agent is a UEA-type expansion agent, and the specific surface area of the slag powder is ≥400m 2 / kg, flow ratio ≥95%, in line with the standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete", the aggregate is standard sand, specifically IS0 standard sand; (3) The slurry prepared in step (2) is introduced into a mold and placed in a standard constant temperature and humidity curing box in an environment with a temperature of 21°C and a humidity of 95% for 2 hours. After demolding, it is continued to be placed in the constant temperature and humidity curing box for curing.
[0040] Figure 1 The scanning electron microscope image of the geopolymer prepared in this example after being placed in a natural environment for 60 days shows that the geopolymer has a uniform and dense structure. Figure 2 and Figure 3 Scanning electron micrographs of geopolymers prepared by adding 0.3% hydroxypropyl ethylcellulose and 1.0% ethylene-vinyl acetate copolymer after being naturally placed for 60 days. It can be seen that after the geopolymer has been placed for a period of time, obvious cracks appear in the structure.
[0041] The slurry was prepared by mixing the components in Example 1, and the use of water-soluble polymer materials was adjusted, specifically hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer were used alone for doping. In the test of adding polymer materials alone, the optimal doping amount of hydroxypropyl ethyl cellulose was 0.3%, the optimal doping amount of polyethylene oxide was 0.1%, and the optimal doping amount of ethylene-vinyl acetate copolymer was 3.0%. By adjusting the doping amount of the polymer composition, the influence of the polymer composition on the strength of the prepared geopolymer was tested, and the results are shown in Table 2. In the composition, hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer are respectively recorded as Z1, Z2 and Z3.
[0042] Table 2:
[0043] Using Bayer red mud as raw material, the effect of adding polymer materials on the compressive strength of the prepared geopolymer is as follows: Figure 5-7 As shown in the figure, when each component of the polymer material is added alone, at a certain addition amount, the compressive strength of the prepared geopolymer is improved to a certain extent. Figure 5 As shown in the figure, when the doping amount of hydroxypropyl ethyl cellulose is between 0.05% and 0.5%, as the doping amount increases, the compressive strength of the prepared geopolymer increases first and then decreases. When the doping amount is 0.3%, the compressive strength of the prepared geopolymer is optimal, reaching 42.4Mpa after 28 days. Figure 6 As shown, when the polyethylene oxide doping amount is between 0.05% and 0.4%, the compressive strength of the prepared geopolymer first increases and then decreases. When the doping amount is 0.1%, the compressive strength is optimal, which is 42.2 MPa. Figure 7 As shown in the figure, when the doping amount of ethylene-vinyl acetate copolymer is between 0.5% and 4.0%, it first increases and then decreases. When the doping amount is 1.0%, the effect is the best. At 28 days, the compressive strength can reach 41.6Mpa. As the doping amount increases, the compressive strength decreases significantly. When the doping amount reaches 4.0%, the decrease is most significant. The compressive strength at 28 days drops to 35.9MPa, which is lower than the compressive strength without addition, and then the decrease slows down.
[0044] After Z1, Z2 and Z3 were compounded, the optimal doping amount of Z1 was 0.2%, and the optimal doping amount of Z2 was 0.1%. Among them, when the doping amount of ethylene-vinyl acetate copolymer increased from 1.0% to 4.0%, the compressive strength of the prepared geopolymer showed a trend of first increasing and then decreasing. It reached the highest when the doping amount reached 2.0% (Example 1), increasing to 50.6MPa. When the doping amount was further increased to 3.0%, the strength decreased significantly. Continuing to increase the doping amount of Z3, the strength decreased more significantly, so no further testing was carried out.
[0045] Solidification heavy metal ion test: Before the leaching test, the red mud base polymer was cured for 28 days. The heavy metal leaching test was carried out in accordance with the "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ557-2010). The sample with a dry weight of 100g was weighed and placed in a wide-mouth bottle with a screw cap and an inner cap. According to the moisture content of the sample, the volume of the required leaching agent was calculated at a liquid-solid ratio of 10:1 (L / kg). The leaching agent was added, and the bottle cap was tightly fixed vertically on the horizontal oscillation device. The oscillation frequency was adjusted to 110±10 times / min and the amplitude was 40 mm. After oscillating at room temperature for 8 hours, the extraction bottle was removed and allowed to stand for 16 hours. The leaching solution was obtained by filtration using a vacuum filtration device, and the heavy metal content in the leaching solution was tested by ICP-MS. The results are shown in Table 3.
[0046] Table 3:
[0047] It can be seen that in the geopolymer prepared by adding a single polymer material, the dissolution concentration of heavy metal ions Cr, Cu and Ni did not change significantly compared with the geopolymer without addition. However, after adding the three polymer materials in combination, the dissolution concentration of heavy metal ions decreased significantly, which shows that the addition of the polymer composition effectively improves the curing effect of the geopolymer on heavy metal ions.
[0048] On the basis of Example 1, by adjusting the proportion of red mud in the cementitious material, the strength change of the prepared geopolymer was detected. The results are shown in Table 4.
[0049] Table 4:
[0050] Example 2 A method for preparing a high-performance low-carbon red mud-based polymer comprises the following steps: (1) The dried Bayer red mud was crushed, passed through a 40-mesh sieve, calcined at 800°C for 1 hour and then cooled naturally; (2) The Bayer red mud treated in step (1) and the slag powder are mixed in a mass ratio of 0.4:0.6 as a cementitious material, the cementitious material, the alkali activator, the water reducer, the retarder, the expansion agent and the polymer composition are mixed, water is added and stirred evenly, and then the aggregate is added and stirred evenly to form a slurry, and the water-cement ratio is 0.55; the mass ratio of the cementitious material to the aggregate is 1: 2. Based on the mass of cementitious materials, according to the mass percentage, the alkali activator is 7.5% in terms of Na2O, the water reducer is 0.4%, the retarder is 2%, the expansion agent is 0.5%, and the polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer, and the doping amounts are 0.2% hydroxypropyl ethyl cellulose, 0.1% polyethylene oxide and 2.0% ethylene-vinyl acetate copolymer respectively; the aggregate is ISO standard sand, the alkali activator is instant sodium silicate powder, the solution modulus is adjusted to 2.5 with sodium hydroxide, the water reducer is sodium lignin sulfonate, the retarder is calcium stearate, the expansion agent is AEA type concrete expansion agent, and the specific surface area of the slag powder is ≥400m 2 / kg, flow ratio ≥95%, in accordance with the standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete" The aggregate is standard sand, specifically IS0 standard sand; (3) The slurry prepared in step (2) is introduced into a mold and placed in a standard constant temperature and humidity curing box in an environment with a temperature of 21°C and a humidity of 95% for 2 hours. After demolding, it is continued to be placed in the constant temperature and humidity curing box for curing.
[0051] Figure 4 This is a scanning electron microscope image of the geopolymer prepared in this example after being placed in a natural environment for 60 days. After being placed for a long time, the geopolymer still maintains a compact structure.
[0052] According to the method in this embodiment, by adjusting different polymer material additives, the compressive strength and heavy metal ion curing effect of the prepared geopolymer are shown in Table 5.
[0053] Table 5:
[0054] Example 3 A method for preparing a high-performance low-carbon red mud-based polymer comprises the following steps: (1) The dried Australian Bayer red mud was crushed, passed through a 40-mesh sieve, calcined at 700°C for 1.5 h, and then cooled naturally; (2) The Bayer red mud treated in step (1) and the slag powder are mixed in a mass ratio of 0.7:0.3 as a cementitious material, the cementitious material, the alkali activator, the water reducer, the retarder, the expansion agent and the polymer composition are mixed, water is added and stirred evenly, and then the aggregate is added and stirred evenly to form a slurry with a water-cement ratio of 0.35; the mass ratio of the cementitious material to the aggregate is 1:3, and based on the mass of the cementitious material, in the slurry, according to the mass percentage, the alkali activator is 6.5% in terms of Na2O, the water reducer is 1.2%, the retarder is 2.5%, and the expansion agent is 1.6%. The polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer, and the doping amounts are 0.3% hydroxypropyl ethyl cellulose, 0.4% polyethylene oxide and 1.0% ethylene-vinyl acetate copolymer respectively; the aggregate is ISO standard sand, the alkali activator is instant sodium silicate powder, the solution modulus is adjusted to 1.0 with sodium hydroxide, the water reducer is polycarboxylate water reducer, the retarder is dodecyl trimethoxy silane, the expansion agent is UEA type concrete expansion agent, and the specific surface area of the slag powder is ≥400m 2 / kg, flow ratio ≥95%, in accordance with the standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete" The aggregate is standard sand, specifically IS0 standard sand; (3) The slurry prepared in step (2) is introduced into a mold and placed in a standard constant temperature and humidity curing box in an environment with a temperature of 21°C and a humidity of 95% for 2 hours. After demolding, it is continued to be placed in the constant temperature and humidity curing box for curing.
[0055] The compressive strength and heavy metal ion curing effect of the geopolymer prepared in this example are shown in Table 6.
[0056] Table 6:
Claims
1. A method for preparing a high-performance low-carbon red mud-based polymer, comprising the preparation of a slurry, characterized in that: The slurry is prepared by crushing dried Bayer red mud and then calcining it, mixing the calcined red mud with slag powder as a cementitious material, mixing the cementitious material, aggregate, alkali activator and external additives, adding water and stirring evenly to form a slurry, wherein the external additive includes a polymer composition, and the polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer.
2. A method for preparing a high-performance low-carbon red mud-based polymer according to claim 1, characterized in that: The addition amount of each component in the polymer composition is based on the mass of the gelling material, and is calculated by mass percentage. The doping amount is 0.05%-0.5% of hydroxypropyl ethyl cellulose, 0.05%-0.4% of polyethylene oxide, and 0.5%-3% of ethylene-vinyl acetate copolymer.
3. A method for preparing a high-performance low-carbon red mud-based polymer according to claim 1 or 2, characterized in that: The calcination is to calcine the crushed Bayer red mud at 600-800° C. for 1-2 h, and then naturally cool it to room temperature.
4. A method for preparing a high-performance low-carbon red mud-based polymer according to any one of claims 1 to 3, characterized in that: In the cementitious material, the mass ratio of Bayer red mud to slag powder is 0.4: 0.6-0.7: 0.3, and the slag powder is at least one of S95 slag powder and S105 slag powder.
5. A method for preparing a high-performance low-carbon red mud-based polymer as claimed in claim 4, characterized in that: The alkaline activator is instant sodium silicate powder, and the solution modulus is adjusted to 1.0-2.5 with sodium hydroxide.
6. A method for preparing a high-performance low-carbon red mud-based polymer according to any one of claims 1 to 5, characterized in that: The external additives also include water reducing agent, retarder and expansion agent.
7. A method for preparing a high-performance low-carbon red mud-based polymer according to claim 6, characterized in that: The water reducer is at least one of sodium lignin sulfonate, polycarboxylic acid water reducer, naphthalene water reducer, and melamine water reducer; the retarder is at least one of sodium gluconate, boric acid, sucrose, calcium stearate, dodecyltrimethoxysilane, desulfurized gypsum, etc.; the expansive agent is at least one of UEA type and AEA type concrete expansive agent.
8. A method for preparing a high-performance low-carbon red mud-based polymer as claimed in claim 6 or 7, characterized in that: In the prepared slurry, the mass ratio of cementitious material to aggregate is 1:1-3. Based on the mass of cementitious material, the alkali activator in the slurry is 6.5%-7.5% in terms of Na2O, the water reducer is 0.4%-1.2%, the retarder is 2%-3%, the expansion agent is 0.5%-1%, and the water-cement ratio of the slurry is 0.35-0.
55.
9. A method for preparing a high-performance low-carbon red mud-based polymer, characterized in that: The steps include: (1) Grind the dried Bayer red mud, pass it through a 40-mesh sieve, calcine it at 600-800°C for 1-2h and then cool it naturally; (2) The Bayer red mud treated in step (1) and the slag powder are mixed in a mass ratio of 0.4: 0.6-0.7:0.3 as a cementitious material, the cementitious material, the alkali activator, the water reducer, the retarder, the expansion agent and the polymer composition are mixed, water is added and stirred evenly, and then the aggregate is added and stirred evenly to form a slurry, and the water-cement ratio is 0.35-0.55; the mass ratio of the cementitious material to the aggregate is 1:1-3, based on the mass of the cementitious material, in terms of mass percentage, the alkali activator is 6.5%-7.5% in terms of Na2O, the water reducer is 0.4%-1.2%, the retarder is 2%-3%, the expansion agent is 0.5%-1%, and the polymer composition is composed of hydroxypropyl ethyl cellulose, polyethylene oxide and ethylene-vinyl acetate copolymer. The composition is as follows: the doping amounts are 0.05% to 0.5% of hydroxypropyl ethyl cellulose, 0.05% to 0.4% of polyethylene oxide, and 0.5% to 3% of ethylene-vinyl acetate copolymer; the aggregate is ISO standard sand; the alkali activator is instant sodium silicate powder; the solution modulus is adjusted to 1.0 to 2.5 with sodium hydroxide; the water reducer is at least one of sodium lignin sulfonate, polycarboxylic acid water reducer, naphthalene water reducer, and melamine water reducer; the retarder is at least one of sodium gluconate, boric acid, sucrose, calcium stearate, dodecyl trimethoxy silane, desulfurized gypsum, etc.; the expansion agent is at least one of UEA type and AEA type concrete expansion agent; (3) The slurry prepared in step (2) is introduced into a mold and placed in a constant temperature and humidity curing box for 2 hours. After demolding, it is continued to be placed in the constant temperature and humidity curing box for curing.
Citation Information
Patent Citations
Premixed and pumped heavy concrete
CN101676239A
Method for producing geopolymer binding material by red mud and geopolymer binding material
CN103964710A
Red stucco finish prepared by red mud-based alkali-activated cementing material
CN105174755A
Lightweight sound insulation self-insulating wall body filling additive, slurry and preparation method thereof
CN108751782A
Sludge curing agent using Portland cement and production method of sludge curing agent
CN112341126A
Cited By
Geopolymer concrete for improving construction performance based on excitant pretreatment and preparation method of geopolymer concrete
CN121021058A